Burton Mack’s Challenge to the Study of Religion - Braun, Willi (2023)
Burton Mack was the most influential and, perhaps, controversial scholar of the Christian bible and Christian origins of his generation. He exposed the conventional story of Christian origins as a myth that needed to be studied not on its own terms but in terms of a general theory of religion that would be useful also in the study of religions other than Christianity. This article provides a brief summary of the main features of Mack’s work for readers who are not familiar with it. Its purpose is also to be a setup for a set of essays that engage Mack in their own areas of specialization in the study of religion.
Keywords: mythmaking; Social formation; Christian Origins; Burton Mack